LINGUISTIC FEATURES OF TOPONYMS REPRESENTED BY COMPOUND NOUNS IN DIFFERENT SYSTEMATIC LANGUAGES - Ismatova Nodirakhon Makhmudovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The following article demonstrates some features of toponimic words which are represented by different systematic language. Moreover, the article shows toponimic features of the compound noun and gives background information about toponymy.